Análise fitoquímica, antioxidante e fitotóxica dos extratos de folhas de salvia officinalis l. sobre lycopersicon esculentum - Silva, Claudia Tatiana Araujo da Cruz (2016)
Allelochemicalare substances present in plants, released into the environment that influence on the community, since the allelopathic potential of one plant can inhibit the development of others. Medicinal plants that have essential oils in their composition have typically been promising in weed control. Thus, this study evaluated the phytotoxic potential of dried leaves, extracts and essential oil of sage on germination and growth of tomato, guinea grass and chia plants, under laboratory conditions and at greenhouse as well as identified the chemical composition and antioxidant activity. For the bioassays in laboratory, dried leaves were soaked using hexane, ethyl acetate, acetone and methanol solvents and extracts were submitted to reactions for phytochemical characterization. The essential oil was obtained by hydro-distillation of leaves and its composition was determined by gas chromatography coupled to mass spectrometry. Antioxidant activity was measured by free radicals as DPPH. Allelopathic tests used extracts at 1% concentration and essential oil at concentrations of 0, 100, 200, 400, 600, 800, 1,000 and 2,000 mg L-1 (v/v). In greenhouse, dry mass of sage was tested at 3.75; 7.5 and 15 t ha-1 rates and the control (no mass). Phytochemical analysis revealed the occurrence of tannins, flavonoids, saponins and triterpenoids on extracts. Acetone and methanolic extracts have registered some high antioxidant activity. All extracts reduced tomato germination parameters and the extracts produced with hexane and ethyl acetate also reduced tomato shoot growth. The acetone extract had no effect on germination of guinea grass, while other extracts tested inhibited the answers and hexane extract decreased seedling growth of this specie. Hexane extract reduced the germination of chia seeds. However, the other parameters of germination were affected by the other extracts without any effect on growth. Twenty-eight compounds were recorded (corresponding to 98.82% essential oil) and the highest were: camphor (27.59%), camphene (23.70%), α-pinene (13.75%), β-pinene (6.28%) and limonene (5.38%). Monoterpenes (68%) have been prevalent in essential oil. The essential oil showed 85.3% of DPPH radical seizing activity and a 3.67 μg mL-1IC50value characterizing it as a great antioxidant. The final germination percentage of the three species was not inhibited by the essential oil at the tested concentrations. However, germination speed, time indices and average speed of germination rates were adversely affected in most tested concentrations for tomato and chia seeds. The same behavior was not observed for guinea grass seeds. In greenhouse, chlorophyll contents of tomato and guinea grass plants were reduced with 7.5 and 15 t ha-1 sage as cover crop. Tomato shoot length was inhibited in all tested rates, and guinea grass plants showed some growth decrease when using 15 t ha-1 sage mass. The dry mass of tomato plants was reduced when 15 t ha-1 sage and 7.5 and 15t ha-1 guinea grass were used as cover crops. In general, the extracts showed better phytotoxic activity to parameters of germination than the seedling growth. The effect varied due to the target specie and solvent used to prepare the extract. Sage as cover crop reduced the evaluated variables in tomato and guinea grass, but there was no effect on chia plants. It is suggested that planting in sequence or too close must be avoided. On the other hand, the essential oil showed no influence on guinea grass seeds. But, it is worth noting that botanical species respond differently and, usually, there is no allelopathic effect on germination percentage